Non-Aβ Component of Alzheimer’s Disease Amyloid (NAC) Revisited : NAC and α-Synuclein Are Not Associated with Aβ Amyloid - Culvenor, Janetta G. (American Society for Investigative Pathology, 1999)
α-Synuclein (αSN), also termed the precursor of the non-Aβ component of Alzheimer’s disease (AD) amyloid (NACP), is a major component of Lewy bodies and Lewy neurites pathognomonic of Parkinson’s disease (PD) and dementia with Lewy bodies (DLB). A fragment of αSN termed the non-Aβ component of AD amyloid (NAC) had previously been identified as a constituent of AD amyloid plaques. To clarify the relationship of NAC and αSN with Aβ plaques, antibodies were raised to three domains of αSN. All antibodies produced punctate labeling of human cortex and strong labeling of Lewy bodies. Using antibodies to αSN(75–91) to label cortical and hippocampal sections of pathologically proven AD cases, we found no evidence for NAC in Aβ amyloid plaques. Double labeling of tissue sections in mixed DLB/AD cases revealed αSN in dystrophic neuritic processes, some of which were in close association with Aβ plaques restricted to the CA1 hippocampal region. In brain homogenates αSN was predominantly recovered in the cytosolic fraction as a 16-kd protein on Western analysis; however, significant amounts of aggregated and αSN fragments were also found in urea extracts of SDS-insoluble material from DLB and PD cases. NAC antibodies identified an endogenous fragment of 6 kd in the cytosolic and urea-soluble brain fractions. This fragment may be produced as a consequence of αSN aggregation or alternatively may accelerate aggregation of the full-length αSN.